Evaluation and trend of fashion design research: visualization analysis based on CiteSpace - Yixin Zou; Sarawuth Pintong; Tao Shen; Ding-Bang Luh (Fashion and Textiles, 2022)
Abstract Fashion or apparel refers to a topic discussed publicly as an indispensable discipline on a day-to-day basis, which has aroused rising attention from academic sessions over the past two decades. However, since the topic of fashion design covers knowledge in extensive ranges and considerable information, scholars have not fully grasped the research field of fashion design, and the research lacks directional guidance. To gain more insights into the existing research status and fronts in the fashion design field, this study conducts a quantitative literature analysis. The research of this study is conducted by employing CiteSpace technology to visualize and analyze 1388 articles regarding “fashion design” in the Web of Science (WOS) Core Collection. To be specific, the visualization and the analysis concentrate on the annual number of articles, author collaboration, institutional collaboration, literature citations, keywords clustering, and research trend evolution of the mentioned articles. As highlighted by this study, the effect of the US and the UK on academic research in fashion design is relatively stronger and extensive. Sustainable fashion refers to the research topic having aroused more attention since 2010, while new research topics over the past few years consist of “wearable fashion”, “transgender fashion” and “medical fashion”. The overall research trend of fashion design is developing as interdisciplinary cross research. This study systematically reviews the relevant literature, classifies the existing research status, research hotspots and frontier trends in the academic field of “fashion design”, and presents the knowledge map and information of literature for researchers in relevant fields.